(untitled) (CIPEEX, 2024)
IN THIS ARTICLE, WE TAKE A DETAILED LOOK AT THE IMPACTS OF THE COVID-19 PANDEMIC ON BRAZILIAN PRISONS, WITH THE AIM OF INVESTIGATING THE CONSEQUENCES OF THE SPREAD OF THE VIRUS IN TERMS OF PUBLIC HEALTH, HUMAN RIGHTS AND SECURITY. THROUGH THE USE OF QUALITATIVE RESEARCH METHODS, THE RESULTS OBTAINED REVEAL THAT POOR HYGIENE CONDITIONS AND OVERCROWDING HAVE MADE LOCAL PRISONS A FAVORABLE ENVIRONMENT FOR THE LARGE-SCALE SPREAD OF COVID-19. THE MEASURES ADOPTED TO CONTAIN THE SPREAD OF THE VIRUS, SUCH AS THE SUSPENSION OF VISITS AND OUTSIDE ACTIVITIES, HAVE EXACERBATED EXISTING PROBLEMS, SUCH AS SOCIAL ISOLATION AND ANXIETY AMONG INMATES. GIVEN THIS CONTEXT, IT IS POSSIBLE TO CONCLUDE THAT THE PANDEMIC HAS CRITICALLY EXPOSED THE STRUCTURAL AND MANAGEMENT DEFICIENCIES OF THE BRAZILIAN PRISON SYSTEM. IN THIS SENSE, WE RECOMMEND THE IMPLEMENTATION OF STRATEGIES SUCH AS EMERGENCY RELEASES OF NON-DANGEROUS PRISONERS, IMPROVEMENTS TO PRISON FACILITIES, INCLUDING THE GUARANTEE OF ADEQUATE SANITARY CONDITIONS, AND THE ADOPTION OF STRICT HEALTH PROTOCOLS TO FACE THIS PUBLIC HEALTH CRISIS WITHOUT VIOLATING THE FUNDAMENTAL RIGHTS OF INMATES.